Analysing household decision-making on oil palm cultivation in Thailand. Issue 5 (2nd September 2016) - Nualnoom, Pairote; Wehrmeyer, Walter; Morse, Stephen
ABSTRACT: This paper analyses the dynamics of land use via the perspectives, motivations and behaviours of local landowners looking at land-use change (through the landowner's eyes) in the way that the landowners would prefer to do and not to do in various situations. The dynamics are explored in the context of an oil-palm-based biodiesel development in Thailand where the advent of oil palm (OP) has caused the loss of paddy areas. A sequential mixed-method strategy, including 10 in-depth interviews and 180 responses to a questionnaire survey, indicates that the likelihood of a landowner switching traditional land for OP cultivation is affected by a number of factors including age and education of the head of household, number of household farming labourers, amount and source of income, land size and land right. Moreover, the results indicate that success of switching land to OP cultivation was determined by factors influencing willingness and capacity to change. Willingness-related factors are relevant to outcome expectation and social networks and connections while capacity-related factors are relevant to finance, labour, capital, land rights and transportation.